A kind of preparation method of furfural
By using chlorine-containing sulfonic acid carbon-based solid acid catalyst and biliquid phase reaction medium, the dehydration reaction of xylocarbohydrates is solved, and the problems of low efficiency and pollution in the existing furfural production process are achieved, and furfural production with high selectivity and high yield are achieved.
Patent Information
- Application Number
- CN202111524456.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-14
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-12-14
AI Technical Summary
In the existing furfural production process, the dilute sulfuric acid catalytic system has low efficiency, low yield of furfural, and there are problems of pollution and high cost.
A bi-liquid phase reaction medium consisting of a chlorine-containing sulfonic acid carbon-based solid acid catalyst and a low-boiling organic solvent and a low-eutectic solvent are used to carry out intramolecular dehydration reaction of xylocarbohydrates to improve the selectivity and yield of furfural.
The selectivity and yield of furfural is significantly improved, the residence time of furfural under high-temperature acidic conditions is reduced, and the decomposition is avoided. The catalyst preparation method is simple, green and safe.
Smart Images

Figure BDA0003408689070000061 
Figure BDA0003408689070000062 
Figure BDA0003408689070000071
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing a biomass-based furfural product through sugar carbohydrates, and belongs to the field of fine chemicals. Background Art
[0002] Sugar carbohydrates represented by pentose are an important component of biomass resources. After dehydration reaction, they can obtain an important biomass-based platform molecule compound - furfural, and can be further prepared into high-value-added chemicals and liquid fuels through chemical catalytic conversion, which can effectively replace traditional fossil energy. Therefore, developing a method for efficiently utilizing pentose compounds to prepare furfural is a key issue for the effective utilization of biomass resources.
[0003] At present, the annual furfural production in the world is more than 300,000 tons, and China is the main producer and consumer of furfural. my country uses corn cobs as the main raw material for furfural production. It uses a one-step continuous hydrolysis method to mix the physically pretreated corn cobs with dilute sulfuric acid, and then cook them in series to first obtain sugar monomer molecules, and then dehydrate to obtain furfural-containing steam. Although this method is widely used, it has obvious disadvantages: the efficiency of the dilute sulfuric acid catalytic system is low, and the furfural yield is low, less than 50%; dilute sulfuric acid will corrode the reaction vessel under hydrothermal conditions, requiring a reactor made of special materials, which is expensive; the dilute sulfuric acid system produces serious pollution problems (waste gas, wastewater, and waste residue) during the production process. Therefore, in order to increase the yield of furfural and comply with the principles of green chemistry, it is very necessary for China, as a major producer of furfural, to improve the current production process.
[0004] In the process of furfural production, the acid catalyst and the reaction medium are the two most important factors. For catalysts, solid acid catalysts are easy to separate, have little pollution and corrosion, and have attracted the attention of researchers. Patent CN102391217A discloses a method for preparing furfural by catalyzing the vaporization of straw washing liquid with HZSM-5 molecular sieve solid acid. After optimization, the optimal yield of furfural is 37.5%. Qing et al. (Qing Qing, Qi Guo, Linlin Zhou. et al. Bioresour Technol, 2016, 226, 247-254.) prepared a montmorillonite-loaded SO4 2- / SnO2 solid acid catalyst, corn cob as raw material in toluene / water two-phase system with NaCl as auxiliary agent, reacted at 190℃ for 15min, the furfural yield was 81.7%. After the catalyst was recycled for five times, the furfural yield dropped to 69.46%. Therefore, it is very important to obtain a highly active and stable solid acid catalyst through a simple preparation method for furfural production.
[0005] There are a lot of literature reports on reaction media, among which xylose can be used to obtain furfural in aqueous solution and supercritical aqueous solution system (Motokucho S, Morikawa H, Nakatani H, et al. Tetrahedron Letters 2016, 57: 4742-4745.), organic solvent system (Gomes GR, Rampon DS, Ramos L P. Applied Catalysis A: General, 2017, 545: 127-133.), two-liquid phase reaction system (James A. Dumesic, et al. Science, 2006, 312, 1933-1937) and ionic liquid system (Bekbolat Kassanov JW, Yan F, Jie C. RSC Advances, 2017, 7: 30755-30762.). However, since xylose has a stable six-membered ring structure and is not easy to dehydrate, it is still necessary to further improve the solubility and solvation of the reaction medium for xylose and reduce the activation energy of xylose dehydration. An effective strategy to increase the yield of furfural is to simultaneously improve the reaction performance of the solid acid catalyst and the reaction medium, promote the rapid dehydration of xylose, and reduce the residence time of furfural in the acidic reaction medium. Summary of the invention
[0006] The purpose of the present invention is to overcome the above-mentioned shortcomings of the prior art and provide a method for preparing furfural from xylose-based carbohydrates. The chlorine-containing sulfonic acid carbon-based solid acid catalyst used in the method has a high surface sulfonic acid density, the chlorine group absorbs electrons to enhance the acidity of the catalyst, and the reaction medium has a good dissolution and solvation effect on xylose, thereby improving the reaction performance of the solid acid catalyst and the reaction medium at the same time, significantly reducing the xylose dehydration reaction time, reducing the residence time of the target product furfural in a high-temperature acidic environment, avoiding furfural from decomposing due to long-term residence under high-temperature acidic conditions, thereby improving the selectivity of furfural.
[0007] The present invention provides a method for preparing furfural, comprising:
[0008] In a two-liquid phase reaction medium consisting of a low boiling point organic solvent and a low eutectic solvent, in the presence of a chlorine-containing sulfonic acid carbon-based solid acid catalyst, xylose-based carbohydrates undergo intramolecular dehydration reaction at 80° C.-200° C. to obtain the furfural.
[0009] The chlorine-containing sulfonic acid carbon-based solid acid catalyst is obtained by sulfonating a chlorine-containing resin precursor with a sulfonating agent, wherein the chlorine-containing resin precursor is polymerized from a monomer having a benzene ring structure, and at least one substituent on the benzene ring is a chlorine group or a substituent of a chlorine-containing C1-C3 alkyl or alkylene functional group, such as chloromethyl, chloroethyl, chloropropyl, etc.
[0010] The chlorine group-containing resin precursor is preferably one of polychlorostyrene resin, chloromethyl polystyrene resin, chloroethyl polystyrene resin and polyvinyl chloride benzene resin.
[0011] When the resin precursor containing chlorine groups is subjected to sulfonation reaction with the sulfonating agent, the sulfonic acid group of the sulfonating agent replaces the H atom on the benzene ring of the resin precursor, thereby introducing the sulfonic acid group on the benzene ring monomer of the resin to obtain a chlorine-containing sulfonic acid carbon-based solid acid catalyst. After complete sulfonation, the density of sulfonic acid groups on the surface of the solid acid catalyst is relatively high, generally not less than 1.5 mmol / g, preferably 2-3 mmol / g.
[0012] The chlorine-containing resin precursor does not have a microscopic pore structure and has a small specific surface area. The solid acid catalyst obtained after sulfonation still retains the characteristics of a low specific surface area, which is generally not higher than 2m 2 / g.
[0013] The preparation method of the chlorine-containing sulfonic acid carbon-based solid acid catalyst comprises: uniformly mixing a chlorine-containing resin and a sulfonating agent, stirring and reacting at 20° C.-200° C. to obtain a brown-yellow solid, filtering, washing and drying, and the obtained solid is the chlorine-containing sulfonic acid carbon-based solid acid catalyst.
[0014] The sulfonating agent is selected from one of fuming sulfuric acid, concentrated sulfuric acid and chlorosulfonic acid, preferably chlorosulfonic acid. When the sulfonating agent is chlorosulfonic acid, the reaction temperature is preferably room temperature (20°C-30°C), and hydrogen chloride is generated while introducing the sulfonic acid group on the benzene ring; when the sulfonating agent is fuming sulfuric acid or concentrated sulfuric acid, the reaction temperature is preferably 130°C-150°C, and water is generated while introducing the sulfonic acid group on the benzene ring. Considering the catalyst preparation temperature, reducing energy consumption, etc., the sulfonating agent is preferably chlorosulfonic acid.
[0015] The mass ratio of the chlorine-containing resin precursor to the sulfonating agent is 1:1-100, preferably 1:5-10.
[0016] The sulfonation reaction time is 1-24 hours, preferably 8-12 hours.
[0017] In the xylose carbohydrate dehydration reaction, the organic low boiling point solvent is located in the upper layer of the reaction medium and is selected from one of 1,4-dioxane, tetrahydrofuran, acetonitrile, acetone, butanone, and methyl isobutyl ketone, preferably one of 1,4-dioxane, tetrahydrofuran, and acetonitrile.
[0018] The deep eutectic solvent is a homogeneous solvent composed of a hydrogen bond donor and a hydrogen bond acceptor through a hydrogen bond network, and is located in the lower layer of the reaction medium. The hydrogen bond donor is selected from one of water and a polyol, preferably one of water and a C1-C3 polyol, such as water, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and glycerol (glycerol); the hydrogen bond acceptor is selected from a short carbon chain organic quaternary ammonium salt, preferably one of a C1-C4 substituted or unsubstituted hydrocarbon trimethyl quaternary ammonium chloride (chloride), more preferably one of tetramethylammonium chloride, choline chloride, choline chloride (chlormequat), allyl trimethyl ammonium chloride, and butyl trimethyl ammonium chloride.
[0019] The mass ratio of the hydrogen bond acceptor to the hydrogen bond donor of the low eutectic solvent is 0.1-5, preferably 1.5-3.0, and the volume proportion of the low eutectic solvent in the two-liquid phase reaction medium is 5%-50%, preferably 10%-25%.
[0020] The xylosyl carbohydrate is selected from one of purified xylose, crude xylose, xylan, xylose syrup, hemicellulose and industrial hemicellulose.
[0021] The mass ratio of the xylosyl carbohydrate to the two-liquid phase reaction medium is 1:1-1000, preferably 1:5-100, and more preferably 1:5-20.
[0022] The mass ratio of the chlorine-containing sulfonic acid carbon-based solid acid catalyst to the xylose-based carbohydrate is 1:1-100, preferably 1:2-50, and more preferably 1:5-10.
[0023] The temperature of the xylose carbohydrate dehydration reaction is 80°C-200°C, preferably 100°C-150°C, more preferably 110°C-130°C; the time of the xylose dehydration reaction is 0.1-12 hours, preferably 0.2-5 hours, more preferably 0.3-1 hour. The dehydration reaction does not require additional pressurization or separate control of the reaction pressure, and can be carried out in a closed reactor under the pressure naturally generated in the temperature range.
[0024] According to the method of the present invention, the xylose dehydration reaction process is carried out under stirring.
[0025] The reactor required for the xylose dehydration reaction process can be a thick-walled pressure-resistant bottle, a stainless steel reactor with a polytetrafluoroethylene liner, and a reactor that can be easily conceived by a person skilled in the art.
[0026] After the xylose dehydration reaction is completed, the conversion rate of the reaction substrate, the selectivity and yield of furfural during the reaction process can be analyzed and calculated by high performance liquid chromatography.
[0027] The present invention has the following advantages:
[0028] The preparation method of the chlorine-containing sulfonic acid carbon-based solid acid catalyst used in the present invention is simple, green and safe, the sulfonic acid density on the catalyst surface is high, and the electron-withdrawing effect of the chlorine group can improve the sulfonic acid strength on the catalyst surface. The reaction medium used has good solubility for xylose and a high degree of xylose solvation, which can simultaneously improve the reaction performance of the solid acid catalyst and the reaction medium, reduce the residence time of furfural under high temperature acidic conditions, avoid furfural from being decomposed, and improve furfural selectivity. DETAILED DESCRIPTION
[0029] Preparation Example 1
[0030] 3 g of chloromethyl polystyrene resin (purchased from Fluorochem) was placed in a round-bottom flask, and then 30 g of chlorosulfonic acid was added to the round-bottom flask, sealed and mixed evenly, and stirred at room temperature for 12 hours. After the sulfonation was completed, the brown-yellow solid in the round-bottom flask was filtered through a filter membrane, and then washed thoroughly with hot deionized water (>80°C) and ethanol until the filtrate was neutral, and the filtrate was subjected to a BaCl2 test to confirm that there was no SO4 2- The washed solid powder was placed in an oven at 120°C and dried for 10 hours. The solid obtained was the chlorine-containing super strong sulfonic acid resin solid acid catalyst, which was recorded as catalyst I. After acid-base titration, the surface sulfonic acid density of catalyst I was 2.40 mmol / g. The molecular structure of catalyst I is as described in preparation formula 1.
[0031] Preparation formula 1:
[0032]
[0033] Preparation Example 2
[0034] The reaction was carried out according to Preparation Example 1, except that the chloromethyl polystyrene resin was replaced with chloroethyl polystyrene resin (purchased from Fluorochem), which was recorded as Catalyst II. After acid-base titration, the sulfonic acid density on the surface of Catalyst III was 2.37 mmol / g. The molecular structure of Catalyst II is as described in Preparation Formula 2.
[0035] Preparation formula 2:
[0036]
[0037] Preparation Example 3
[0038] The reaction was carried out according to Preparation Example 1, except that the chloromethyl polystyrene resin was replaced with polychlorostyrene resin (purchased from Fluorochem), which was recorded as Catalyst III. After acid-base titration, the sulfonic acid density on the surface of Catalyst II was 2.50 mmol / g. The molecular structure of Catalyst III is as described in Preparation Formula 3.
[0039] Preparation formula 3:
[0040]
[0041] Preparation Example 4
[0042] The reaction was carried out according to Preparation Example 1, except that the chloromethyl polystyrene resin was replaced with polyvinyl chloride benzene resin (purchased from Fluorochem), which was recorded as Catalyst IV. After acid-base titration, the sulfonic acid density on the surface of Catalyst III was 2.50 mmol / g. The molecular structure of Catalyst IV is as described in Preparation Formula 4.
[0043] Preparation formula 4:
[0044]
[0045] Preparation Example 5
[0046] The reaction was carried out according to Preparation Example 1, except that chlorosulfonic acid was replaced with concentrated sulfuric acid, and the sulfonation temperature was increased from room temperature to 150°C, which was recorded as Catalyst V. After acid-base titration, the surface sulfonic acid density of Catalyst V was 2.18 mmol / g. The sulfonation mechanism of concentrated sulfuric acid and chlorosulfonic acid is the same, both of which are to replace the sulfonic acid group with the hydrogen atom on the benzene ring of chloromethyl polystyrene resin to introduce the sulfonic acid group on the benzene ring. The difference is that chlorosulfonic acid generates hydrogen chloride after the reaction, while concentrated sulfuric acid generates water. Therefore, the structural formula of this catalyst V is as described in Preparation Formula 5.
[0047] Preparation formula 5:
[0048]
[0049] Preparation Example 6
[0050] The reaction was carried out according to Preparation Example 1, except that chlorosulfonic acid was replaced with oleum, and the sulfonation temperature was increased from room temperature to 130°C, which was recorded as Catalyst VI. After acid-base titration, the surface sulfonic acid density of Catalyst VI was 2.20mmol / g. The sulfonation mechanism of oleum and chlorosulfonic acid is the same, both of which are to replace the sulfonic acid group with the hydrogen atom on the benzene ring of chloromethyl polystyrene resin to introduce the sulfonic acid group on the benzene ring. The difference is that chlorosulfonic acid generates hydrogen chloride after the reaction, while oleum generates water. Therefore, the structural formula of this catalyst VI is as described in Preparation Formula 6.
[0051] Preparation formula 6:
[0052]
[0053] Comparative Preparation Example 1
[0054] The reaction was carried out at room temperature according to the method of Preparation Example 1, except that chlorosulfonic acid was replaced with concentrated sulfuric acid, which was recorded as catalyst DI. After acid-base titration, the surface sulfonic acid density of catalyst DI was 0.00 mmol / g.
[0055] Comparative Preparation Example 2
[0056] The reaction was carried out at room temperature according to the method of Preparation Example 1, except that chlorosulfonic acid was replaced with fuming sulfuric acid, which was recorded as Catalyst D II. After acid-base titration, the surface sulfonic acid density of Catalyst D II was 0.00 mmol / g.
[0057] After comparing the acid-base titration results of catalyst I, catalyst V, catalyst VI, catalyst DI and catalyst DII, it was found that under the same room temperature conditions, chlorosulfonic acid can undergo sulfonation reaction with the resin, while concentrated sulfuric acid and fuming sulfuric acid cannot undergo sulfonation reaction with the resin, and no sulfonic acid groups are introduced on the surfaces of catalysts DI and DII. Only after the temperature is raised to 150°C and 130°C can the resin undergo sulfonation reaction with concentrated sulfuric acid, and sulfonic acid groups are introduced on the surfaces of catalysts V and VI. Therefore, when the sulfonating agent is chlorosulfonic acid, it has a stronger sulfonation ability, can undergo sulfonation reaction at room temperature, does not require the introduction of a heat source, and does not produce acidic waste gas, which greatly reduces energy consumption and reduces environmental and safety hazards. Therefore, considering the catalyst preparation conditions, the sulfonating agent is preferably chlorosulfonic acid.
[0058] Test Case
[0059] Catalyst I, Catalyst V and Catalyst VI were placed in a sealed container and water was added. After sealing, the mixture was stirred. Then, the temperature was raised to 150°C and 180°C for hydrothermal treatment. The hydrothermal treatment time was raised to 24 hours. After the treatment, the container was cooled to room temperature, the catalyst was filtered, washed and dried, and then the sulfonic acid density and mass loss on the catalyst surface after the hydrothermal treatment were determined by acid-base titration. The specific results are shown in Table 1.
[0060] Table 1. Catalyst hydrothermal stability results
[0061]
[0062] As can be seen from Table 1, the catalyst I obtained by sulfonation with chlorosulfonic acid at room temperature has better hydrothermal stability than the catalyst V obtained by sulfonation with concentrated sulfuric acid at 150°C and the catalyst VI obtained by sulfonation with fuming sulfuric acid at 130°C. Therefore, considering the hydrothermal stability of the catalyst, the sulfonating agent is preferably chlorosulfonic acid.
[0063] Example 1
[0064] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0065] Add 0.5g of xylose, 0.15g of catalyst I, 0.5mL of water, 1.0g of tetramethylammonium chloride, and 8.5mL of 1,4-dioxane to a 15mL pressure bottle. When the temperature of the multichannel heater is heated to 120°C, place the pressure bottle in the multichannel heater and stir the reaction at a speed of 600r / min for 30 minutes. After the reaction is completed, remove the pressure bottle from the multichannel heater, cool it naturally to room temperature, filter the catalyst, and analyze the reaction solution by high performance liquid chromatography. The conversion rate of xylose is 97.6% and the yield of furfural is 58.9%.
[0066] Example 2
[0067] This example uses Catalyst II to illustrate the method for synthesizing furfural of the present invention.
[0068] The reaction was carried out according to Example 1, except that catalyst I was replaced by catalyst II. The conversion rate of xylose was determined to be 97.7%, and the yield of furfural was 58.0%.
[0069] Example 3
[0070] This example uses Catalyst III to illustrate the method for synthesizing furfural of the present invention.
[0071] The reaction was carried out according to Example 1, except that the catalyst I was replaced by catalyst III. The conversion rate of xylose was determined to be 97.5%, and the yield of furfural was 58.1%.
[0072] Example 4
[0073] This example uses Catalyst IV to illustrate the method for synthesizing furfural of the present invention.
[0074] The reaction was carried out in accordance with Example 1, except that the catalyst I was replaced by catalyst IV. The conversion rate of xylose was determined to be 98.0%, and the yield of furfural was 59.1%.
[0075] Example 5
[0076] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0077] The reaction was carried out in accordance with Example 1, except that the organic solvent 1,4-dioxane was replaced with acetonitrile. The conversion rate of xylose was determined to be 97.3%, and the yield of furfural was 57.6%.
[0078] Example 6
[0079] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0080] The reaction was carried out in accordance with Example 1, except that the organic solvent 1,4-dioxane was replaced with tetrahydrofuran. The conversion rate of xylose was determined to be 96.5%, and the yield of furfural was 57.0%.
[0081] Example 7
[0082] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0083] The reaction was carried out in accordance with Example 1, except that tetramethylammonium chloride was replaced with choline chloride. The conversion rate of xylose was determined to be 97.6%, and the yield of furfural was 58.4%.
[0084] Example 8
[0085] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0086] The reaction was carried out in accordance with Example 1, except that tetramethylammonium chloride was replaced with choline chloride (chlormequat). The conversion rate of xylose was determined to be 97.0%, and the yield of furfural was 58.1%.
[0087] Example 9
[0088] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0089] The reaction was carried out in accordance with Example 1, except that tetramethylammonium chloride was replaced with allyltrimethylammonium chloride. The conversion rate of xylose was determined to be 97.0%, and the yield of furfural was 57.8%.
[0090] Example 10
[0091] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0092] The reaction was carried out according to Example 1, except that tetramethylammonium chloride was replaced with butyltrimethylammonium chloride.
[0093] The conversion rate of xylose was determined to be 96.8%, and the yield of furfural was 57.5%.
[0094] Embodiment 11
[0095] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0096] The reaction was carried out in accordance with Example 1, except that water was replaced by ethylene glycol. The conversion rate of xylose was determined to be 96.7%, and the yield of furfural was 57.6%.
[0097] Example 12
[0098] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0099] The reaction was carried out in accordance with Example 1, except that water was replaced with 1,2-propylene glycol. The conversion rate of xylose was determined to be 96.4%, and the yield of furfural was 58.0%.
[0100] Embodiment 13
[0101] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0102] The reaction was carried out in accordance with Example 1, except that water was replaced with 1,3-propylene glycol. The conversion rate of xylose was determined to be 96.5%, and the yield of furfural was 57.1%.
[0103] Embodiment 14
[0104] This example uses Catalyst I to illustrate the method for synthesizing furfural of the present invention.
[0105] The reaction was carried out in accordance with Example 1, except that water was replaced with glycerol. The conversion rate of xylose was determined to be 96.4%, and the yield of furfural was 58.0%.
[0106] Embodiment 15
[0107] The reaction was carried out according to Example 1, except that 1.0 g of xylose, 0.3 g of catalyst I, 0.8 mL of water, 1.7 g of tetramethylammonium chloride, and 8.0 mL of 1,4-dioxane were added to a 15 mL pressure bottle, and the reaction temperature was raised to 125° C., and the reaction time was extended to 35 minutes. The conversion rate of xylose was determined to be 98.4%, and the yield of furfural was 58.5%.
[0108] Comparative Example 1
[0109] The reaction was carried out according to Example 1, except that Catalyst I was replaced with Amberlyst-15 ion exchange resin (sulfonic acid density: 3.5 mmol / g, without chlorine groups), and the total amount of sulfonic acid groups in the reaction system was the same as that in Example 2 (i.e., 0.24 mmol). The conversion rate of xylose was determined to be 86.6%, and the yield of furfural was 46.3%.
[0110] Comparative Example 2
[0111] The reaction was carried out according to Example 1, except that Catalyst I was replaced with Amberlyst-15 ion exchange resin (sulfonic acid density: 3.5 mmol / g, chlorine-free), the total amount of sulfonic acid groups in the reaction system was kept the same as in Example 2 (i.e., 0.24 mmol), and the reaction time was extended to 50 minutes. The conversion rate of xylose was determined to be 97.8%, and the yield of furfural was 50.7%.
[0112] Comparative Example 3
[0113] The reaction was carried out in accordance with Example 1, except that tetramethylammonium chloride was replaced with octyltrimethylammonium chloride. The conversion rate of xylose was determined to be 95.0%, and the yield of furfural was 50.3%.
[0114] Comparative Example 4
[0115] The reaction was carried out in accordance with Example 1, except that water was replaced with 1,4-butanediol. The conversion rate of xylose was determined to be 97.2%, and the yield of furfural was 51.9%.
[0116] Comparative Example 5
[0117] The reaction was carried out according to Example 1, except that tetramethylammonium chloride was replaced with an equimolar amount of NaCl and the amount of water added was increased to 1.5 mL. The conversion rate of xylose was determined to be 85.4%, and the yield of furfural was 35.9%.
[0118] By comparing the results of Examples 1-4, it can be seen that the surface sulfonic acid group densities of resin precursors with different chlorine groups are roughly the same after complete sulfonation. Therefore, the xylose conversion rate and furfural yield obtained under the same reaction conditions are basically the same, indicating that this type of chlorine-containing sulfonic acid carbon-based solid acid catalyst is universal in the preparation and catalytic dehydration of xylose.
[0119] Comparing the results of Example 1 with Comparative Examples 1 and 2, it can be seen that in the process of catalyzing the xylose to prepare furfural, when the catalyst surface contains chlorine groups, the acidity of the sulfonic acid groups on the catalyst surface is stronger due to the electron-withdrawing effect of the chlorine groups. Therefore, under the condition of the same total amount of sulfonic acid, the solid acid catalyst containing chlorine groups has a faster dehydration rate of xylose, a higher activity, and a shorter time required to reach the same conversion rate. Therefore, the generated target product has a shorter residence time under high temperature acidic conditions, can effectively protect the target product furfural from being further decomposed, and the yield of furfural is higher.
[0120] Comparing the results of Examples 1, 5 and 6, it can be seen that the corresponding xylose conversion rate, furfural selectivity and yield are basically unchanged when using different organic solvents such as 1,4-dioxane, acetonitrile and tetrahydrofuran. If other low-boiling point organic solvents are used, the xylose dehydration rate and furfural yield will be significantly reduced, so the organic solvents in the two-phase reaction medium are preferably 1,4-dioxane, acetonitrile and tetrahydrofuran.
[0121] Comparing the results of Example 1 and Examples 7-10, it can be seen that when tetramethylammonium chloride is replaced with choline chloride, choline chloride (chlormequat), allyltrimethylammonium chloride and butyltrimethylammonium chloride, that is, one methyl side chain (C1) of tetramethylammonium chloride is replaced by a long carbon chain side chain (C2-C4), the xylose dehydration rate and the furfural yield slowly decrease, but the final furfural yield is still higher than 57%, which is better than the current industrial level.
[0122] Comparing the results of Example 1 and Comparative Example 3, it can be seen that when the side chain of the quaternary ammonium salt substituent continues to extend, the furfural yield further decreases, and the surface activity of the hydrogen bond acceptor of the deep eutectic solvent is enhanced due to the increase in the carbon number of the side chain, and at this time, a two-liquid phase reaction system can no longer be formed, but a single-liquid phase reaction system. Therefore, whether from the perspective of the stability of the two-liquid phase system or the furfural yield, the hydrogen bond acceptor of the deep eutectic solvent is selected as a chloride of a C1-C4 substituted or unsubstituted hydrocarbon trimethyl quaternary ammonium salt.
[0123] Comparing the results of Example 1 and Examples 11-14, it can be seen that when water is replaced with ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and glycerol (glycerol), the corresponding xylose conversion rate, furfural selectivity, and yield remain essentially unchanged.
[0124] By comparing the results of Example 1 and Comparative Example 4, it can be seen that when water is replaced with 1,4-butanediol having a longer carbon chain length, the solvation effect of the low eutectic solvent in the lower layer of the two-liquid phase reaction medium on xylose is weakened, and the dehydration rate of xylose and the yield of the target product are reduced. Therefore, the hydrogen bond donor of the low eutectic solvent is preferably water, one of C1-C3 polyols, including one of water, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and glycerol (glycerol).
[0125] Comparing the results of Example 1 and Example 15, it can be seen that when the proportion of the lower layer reaction phase increases and the water content increases, the xylose dehydration rate will be reduced, and a higher temperature, a higher catalyst feed amount, and a longer reaction time are required to achieve similar reaction results. However, it is not advisable to further increase the water amount at this time, because too much water will lead to significant side reactions of xylose and furfural, thereby reducing the yield.
[0126] Comparing the results of Example 1 and Comparative Example 5, it can be seen that when the organic chloride salt tetramethylammonium chloride is replaced by the common inorganic chloride salt NaCl, NaCl is simply dissolved in water and cannot form a hydrogen bond structure with water as a hydrogen bond acceptor, thereby failing to form a low eutectic solvent. Therefore, in order to ensure that the volume of the lower reaction phase remains unchanged, the water content needs to be increased. In addition, since a low eutectic solvent cannot be formed, the solvation effect of the reaction phase on fructose is weakened, the conversion rate of fructose is reduced in the same time, and the furfural yield is also significantly reduced. Therefore, the present invention preferably selects organic chloride salts rather than inorganic chloride salts.
[0127] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0128] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0129] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing furfural, comprising: In a two-liquid phase reaction medium consisting of a low-boiling point organic solvent and a low eutectic solvent, in the presence of a chlorine-containing sulfonic acid carbon-based solid acid catalyst, a xylose-based carbohydrate undergoes an intramolecular dehydration reaction at 80°C-200°C to obtain the furfural; the chlorine-containing sulfonic acid carbon-based solid acid catalyst is obtained by a sulfonation reaction between a chlorine-containing group resin precursor and a sulfonating agent, and the chlorine-containing group resin precursor is selected from one of chloromethyl polystyrene resin, chloroethyl polystyrene resin, polychlorostyrene resin and polyvinyl chloride benzene resin; the low-boiling point organic solvent is located in the upper layer of the reaction medium and is selected from one of 1,4-dioxane, tetrahydrofuran, acetonitrile, acetone, butanone and methyl isobutyl ketone; the low eutectic solvent is a homogeneous solvent composed of a hydrogen bond donor and a hydrogen bond acceptor through a hydrogen bond network, and is located in the lower layer of the reaction medium, wherein the hydrogen bond donor is selected from one of water and a C1-C3 polyol, and the hydrogen bond acceptor is selected from one of a C1-C4 substituted or unsubstituted hydrocarbon trimethyl quaternary ammonium chloride salt.
2. The method according to claim 1, wherein The sulfonic acid group density of the chlorine-containing sulfonic acid carbon-based solid acid catalyst is 2-3 mmol / g.
3. The method according to claim 1, wherein: The sulfonating agent is selected from one of oleum, concentrated sulfuric acid and chlorosulfonic acid.
4. The method according to claim 1, wherein The low boiling point organic solvent is selected from one of 1,4-dioxane, tetrahydrofuran and acetonitrile.
5. The method according to claim 1, wherein: The hydrogen bond acceptor of the deep eutectic solvent is selected from one of tetramethylammonium chloride, choline chloride, choline chloride, allyltrimethylammonium chloride and butyltrimethylammonium chloride.
6. The method according to claim 1, wherein The mass ratio of the hydrogen bond acceptor to the hydrogen bond donor of the low eutectic solvent is 0.1-5:
1.
7. The method according to claim 1, wherein: The mass ratio of the hydrogen bond acceptor to the hydrogen bond donor of the low eutectic solvent is 1.5-3.0:
1.
8. According to the method of claim 1, the volume proportion of the low eutectic solvent in the two-liquid phase reaction medium is 5%-50%.
9. According to the method of claim 1, the volume proportion of the deep eutectic solvent in the two-liquid phase reaction medium is 10%-25%.
10. The method according to claim 1, wherein: The xylosyl carbohydrate is selected from the group consisting of purified xylose, crude xylose, xylan, xylose syrup and hemicellulose.
11. The method according to claim 1, wherein: The mass ratio of the xylose-based carbohydrate to the two-liquid phase reaction medium is 1:1-1000.
12. The method according to claim 1, wherein: The mass ratio of the xylose-based carbohydrate to the two-liquid phase reaction medium is 1:5-100.
13. The method according to claim 1, wherein: The mass ratio of the xylose-based carbohydrate to the two-liquid phase reaction medium is 1:5-20.
14. The method according to claim 1, wherein: The mass ratio of the chlorine-containing sulfonic acid carbon-based solid acid catalyst to the xylose-based carbohydrate is 1:1-100.
15. The method according to claim 1, wherein: The mass ratio of the chlorine-containing sulfonic acid carbon-based solid acid catalyst to the xylose-based carbohydrate is 1:5-10.
16. The method according to claim 1, wherein: The temperature of the xylose-based carbohydrate dehydration reaction is 100° C.-150° C., and the time of the xylose dehydration reaction is 0.2-5 hours.
17. The method according to claim 1, wherein: The temperature of the xylose-based carbohydrate dehydration reaction is 110° C.-130° C., and the time of the xylose dehydration reaction is 0.3-1 hour.
Citation Information
Patent Citations
Method for preparing furaldehyde from steam exploded stalk rinse solution catalyzed by using solid acid with added polymerization inhibitor
CN102391217A
Method for preparing furfural by catalyzing xylose by using acid catalyst
CN104193704A
Preparation method of solid strong acid catalyst and preparation method of furfural
CN107185590A